„O admirande apium fervor!“: Zu Symbolik und ‚Agency‘ der Biene in der beneventanischen Osterliturgie - Utz, Judith (Das Mittelalter, 2023)
The bee was allegorically charged in the Christian Middle Ages: it was considered a symbol of Mary’s virginity. Some regional Easter Vigil liturgies emphasise this in particular. In southern Italy, from the 10th century onwards, a new medium emerged to mark the significance of the Easter Vigil as the climax of the liturgical year. The vertically inscribed and illustrated parchment scrolls, so-called Exultet rolls, were furthermore important for the ecclesiastical and civil communities. This chant of the Easter Vigil prioritises the bee and its polis, thus transferring an ancient topos to Christian liturgy. This essay aims to trace this transfer, focusing on the agency of bees. The fact that such a significant liturgical text is concerned with a non-human animal is extremely unusual and has not yet been studied from the perspective of Human-Animal Studies.
Gesehen am 14.02.2024